Problems of Adherence to Drug Therapy in Medical Rehabilitation (Texas Journal of Medical Science, 2023)
Compliance is defined as “patient compliance with the treatment regimen and regimen.” Low compliance is a complex problem that can have both internal and external causes. It is customary to distinguish four groups of reasons: patient-related factors; therapy-related factors; factors associated with the doctor and factors associated with the environment (social aspect).